2020
DOI: 10.3390/app10217725
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Rice Straw and Whole-Crop Barley (Hordeum vulgare L.) Silage Supplements on Performance and Carcass Characteristics of Hanwoo (Bos taurus coreanae) Steers

Abstract: This study aimed to analyze the effects of whole-crop barley silage (WCBS) and a high-concentrate diet combination to replace a rice straw/concentrate on growth performance, and meat quality of Hanwoo steers (HS). Twenty-four animals were allocated to two groups with a rice straw/concentrate control treatment (CON) and a WCBS/concentrate treatment group. The concentrate was offered to all animals based on live weight after a feeding trial of grass-based diets. Feed intake of WCBS was lower than the CON (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…On the contrary, there is a negative relationship between the dietary concentrate to forage ratio and the IMF content in Hanwoo cattle ( Ku et al., 2021 ). Yang et al. (2020) also concluded that different whole-crop barley silage to concentrate ratio intakes during fattening periods did not cause any significant difference in MS of Hanwoo steers.…”
Section: Nutritional Factorsmentioning
confidence: 87%
“…On the contrary, there is a negative relationship between the dietary concentrate to forage ratio and the IMF content in Hanwoo cattle ( Ku et al., 2021 ). Yang et al. (2020) also concluded that different whole-crop barley silage to concentrate ratio intakes during fattening periods did not cause any significant difference in MS of Hanwoo steers.…”
Section: Nutritional Factorsmentioning
confidence: 87%